Impacts of natural calamity on livelihood of ethnic minority in Lao Cai Province - Luu, Dao Thi; Huong, Le Van (Vietnam Journal of Earth Sciences, 2014)
This article presents survey results about livelihood status and impacts of natural calamities on livelihood of ethnic minorities in Lao Cai province in recent years. Lao Cai is located in northern mountainous region of Vietnam. There are 25 ethnic minorities living with more than 12 kinds of livelihood. Among them, agricultural livelihood plays an important role in life of local people. However, many kinds of natural calamities often occur in Lao Cai, especially, forest fire, damaging cold - extreme cold, flash floods, pipe floods,… happen extremely. They caused extremely serious damage to socio-economic development, especially for livelihood of ethnic minorities there.